HADHANAH DALAM PERSPEKTIF HUKUM KELUARGA ISLAM - Julianti, Rizka; Julianti, Rohmat; Julianti, Kartika (LPPM Universitas Islam Ibrahimy Banyuwangi, 2026)
This study examines the implementation of hadhanah from the perspective of Islamic Family Law and its implications for the fulfillment of children’s rights. It employs a qualitative method with normative and empirical approaches. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that hadhanah practices in Tambangan Kelekar Village, Gelumbang District, Muara Enim Regency, South Sumatra, involve five children whose care is not directly provided by their biological parents but is delegated to relatives such as grandparents, aunts, cousins, or older siblings. This reflects limited parental involvement in meeting children’s physical, emotional, and social needs. From the perspective of Islamic Family Law, such practices do not fully represent the proper fulfillment of parental obligations. This study contributes by strengthening empirical insights into local hadhanah practices and offering conceptual recommendations to promote the best interests of the child as a guiding principle in childcare.